Effect of Topical Steroids on Skin Prick Test: A Randomized Controlled Trial - Ebbesen, Anne R. (Dermatol Ther (Heidelb), 2018)
INTRODUCTION: Topically applied corticosteroids on the skin can significantly inhibit the wheal response to allergens in skin prick test (SPT). The duration of this effect is unknown. The aim of this study is to investigate the duration of the inhibitory effect of topical corticosteroids on SPT. METHODS: Twenty-two healthy subjects were included in a single-blinded randomized study. All subjects were skin prick tested using a standard inhalant allergen panel. The subjects were randomized to treat either the left or right forearm with Betnovat(®) cream (group III steroid) once a day for 10 days. Subsequently, the subjects were skin prick tested the following 5 days and at day 8 on both forearms. RESULTS: At baseline, the 22 individuals had positive SPT for a total of 72 allergens. Compared with the untreated arm, the mean size of the wheals was significantly reduced on day 1 (12 h after end of treatment) by 0.56 mm (95 % confidence interval (CI) [0.06; 1.06], p = 0.03) for allergens and 0.70 mm [0.32; 1.09] (p = 0.001) for histamine. On day 2 (36 h after end of treatment), the mean difference between treated and untreated arm was 0.47 mm [−0.08; 0.85] (p = 0.02) for allergen-induced wheals and 0.22 mm [−0.21; 0.64] (p = 0.31) for histamine-induced wheal. On day 3, 4, 5, and 8, there was no significant difference. CONCLUSIONS: Treatment with topical steroid significantly inhibited the response to SPT for 36 h but for less than 3 days. In addition, we demonstrated that topical applied corticosteroids inhibit the mean wheal size of the positive histamine control for a shorter time than for the allergens. Consequently, positive response to histamine control is not a valid marker for reliable skin prick test in steroid-treated patients. PLAIN LANGUAGE SUMMARY: Plain language summary available for this article.